Role of customer experience and customer engagement in organised retail apparel stores with respect to select cities in Kerala - Kumar, R. Anil; Kinslin, D. (Edelweiss Applied Science and Technology, 2024)
Customer experience (CX) and customer engagement (CE) are pivotal elements in the success of retail stores, influencing customer satisfaction, loyalty, and overall business performance. The present study looks into the role of CX and CE in organized retail apparel stores in select cities of Kerala. Through a mixed-method approach, comprising descriptive as well as correlational research designs, the study investigates how customer experience influences customer engagement, loyalty, and purchase intentions. The findings reveal significant positive impacts of customer experience on engagement and loyalty, with demographic variables playing a moderating role. The results underscore the importance of enhancing customer experience to foster engagement and loyalty, providing strategic insights for retail managers aiming to improve customer retention and satisfaction.